Wealth-Based Fisheries Management: Using Fisheries Wealth to Orchestrate Sound Fisheries Policy in Practice - Cunningham, Stephen (2012)
The importance of resource rent in fisheries has long been acknowledged. By generating such rents, economically efficient management systems increase value added and the sector's contribution to the gross domestic product (GDP) and growth. However, despite the successful adoption of such systems in some countries around the world, economics continues to have relatively little influence on fisheries policy. This lack of influence is particularly noticeable in developing countries, precisely where the contribution that effectively managed fish resources might make to the GDP is most urgently needed. The key requirement to increase the adoption of economically rational fisheries management is to convince policymakers to focus explicitly on the wealth-generating potential offish resources. Such a focus provides a general policy framework within which other approaches, such as rights-based, incentive-based, and ecosystem-based, may be nested. This approach is likely to prove more effective in influencing policy, especially in situations where rights-based systems either will not work or are politically unacceptable.